SURVEY METODE FUSI INFORMASI UNTUK PERANCANGAN COGNITIVE PROCESSOR - Catherine Olivia Sereati; Arwin Datumaya Wahyudi Sumari (Jurnal Ilmiah Teknologi Infomasi Terapan, 2014)
Cognitive  Processor  is  a  processor  which  have  ability  to emulate  how  human  brain  work  to  process  information  by gathering  information  from  the  environment  and  take  the inference from the information that have received. To design Cognitive  processor,  appropriate  methode  is  need  to  support the  performance  of  this  processor.  Knowledge  Growing System (KGS) is a new development of Artificial Intelligence that  have  ability  to  growing  knowledge  base  on  information which  have  been  gathered  as  time  passes.  KGS  concept emerge by observing mechanism of human brain when doing information fusion to gain new knowldege. This paper aimed to  discuss  several  fusion  information  method  as  a  basis  to design Cognitive Processor.